Developing acoustic rating quantities using experimental psychoacoustic data - Virjonen, Petra (fi=Turun yliopisto|en=University of Turku|, 2021)
ABSTRACT Noise is frequently present in our daily lives. Noise is encountered both indoors and outdoors, in various environments such as at home, in traffic and at work place. Excessive noise causes annoyance and other negative health effects. Acoustical quantities are needed to quantify the properties of noise as well as to determine sound insulation capabilities of structures. Psychoacoustic experiments have revealed that the existing quantities do not always correspond well to subjective perception. The objective of this thesis was to develop acoustical quantities that correspond better to subjective perception than the existing quantities by deploying psychoacoustic data. This thesis contains four publications. Three publications consider developing quantities for rating sound insulation, and the fourth deals with annoyance penalty for periodic amplitude modulated sounds. Sound insulation of a structure (e.g. a wall, window, floor, or fac¸ade) is measured in several one-third octave bands. To simplify the information gathered with sound insulation measurements, and to enable easier comparison between structures as well as to facilitate the imposition of legislative requirements, single-number quantities have been developed for rating sound insulation of different structures, such as described in standards ISO 717-1 and ISO 717-2. It is important that these simplified quantities are based on psychoacoustical experiments to ensure adequate correspondence to subjective perception. The development of the existing quantities has not taken this aspect fully into account. In this thesis, single-number quantities for rating sound insulation were developed using mathematical optimization and psychoacoustic data from three already published experiments. New reference spectra were derived for various living sounds for airborne sound insulation, typical domestic impact sounds for impact sound insulation as well as for several road traffic spectra for fac¸ade sound insulation. The results showed that an optimized reference spectrum resulting in well-performing single-number quantity could be derived for each studied sound type. The developed mathematical optimization scheme enables systematic development of new reference spectra, which are based on scientific evidence. Amplitude modulated sounds (e.g. road traffic noise and wind turbine noise) have been found to cause more annoyance than steady-state sounds. A penalty can be added to the measured sound level to take into account the increase in annoyance due to modulation in sound. In this thesis, it was studied if a penalty is needed for periodically amplitude modulated wide-band general sounds having a low sound level by conducting a psychoacoustical experiment with 40 participants. The results showed the need for penalty for certain ranges of modulation frequencies and modulation depths for the studied sounds. The penalties increased with increasing modulation frequency and increasing modulation depth, which does not support using a constant penalty. The results of this thesis can be exploited in the improvement of future academic research, acoustical standards, and building regulations. TIIVISTELMÄ Melu on usein läsnä päivittäisessä elämässämme. Kohtaamme melua erilaisissa ympäristöissä kuten kotona, liikenteessäa ja työpaikoilla. Liiallinen melu häiritsee, ja melun on todettu voivan vaikuttaa myös muilla tavoin negatiivisesti terveyteemme. Akustisten suureiden avulla voidaan määrittää melun ominaisuuksia sekä erilaisten rakenteiden ääneneristyskykyä Psykoakustiset kokeet ovat tuoneet ilmi, että olemassa olevat suureet eivät aina vastaa riittävän hyvin subjektiivista kokemusta melun häiritsevyydestä. Tämän väitöskirjan tarkoituksena oli psykoakustista dataa hyödyntäen kehittää akustisia suureita, jotka vastaavat subjektiivista kokemusta nykyisiä suureita paremmin. Väitöskirjaja koostuu neljästä osajulkaisusta. Kolme julkaisuista käsittelee ääneneristävyyden yksilukuarvojen kehitystä, ja neljäs jaksollisesti moduloitujen äänten häiritsevyyssanktion määrittämistä. Rakenteen (esimerkiksi seinä, ikkuna, lattia tai julkisivu) ääneneristävyys mitataan kolmasosaoktaaveittain useammalla taajuuskaistalla. Monimutkaisen taajuuskaistainformaation yksinkertaistamiseksi on kehitetty yksilukuarvoja (esimerkiksi standardit ISO 717-1 ja ISO 717-2) eri rakenteiden vertailuun sekä mahdollistamaan rakennusmääräysten asettamisen. On tärkeää, että kehitetyt yksilukuarvot perustuvat psykoakustiseen tutkimusnäyttöön, ja vastaavat riittävän hyvin subjektiivista häiritsevyyttä. Nykyisten käytössä olevien standaroitujen suureiden kehityksessä tätä ei ole täysin huomioitu. Tässä väitöskirjassa ääneneristävyyden yksilukuarvoja kehitettiin matemaattisen optimoinnin ja kolmessa jo aiemmin julkaistussa tutkimuksessa kerätyn psykoakustisen datan avulla. Ilmaäänen- ja askeläänieristävyyden referenssispektrit johdettiin erilaisille asuinäänille. Julkisivun ääneneristävyydelle johdettiin referenssispektrit usealle eri tieliikennemeluspektrille. Tulokset osoittivat, että optimoitujen referenssispektrien avulla saadut yksilukuarvot suoriutuivat hyvin kullakin tutkitulla äänityypillä. Kehitetty matemaattinen optimointimalli mahdollistaa tieteelliseen näyttöön perustuvien referenssispektrien ja täten uusien yksilukuarvojen systemaattisen kehityksen. Amplitudimoduloitujen äänien kuten liikennemelun ja tuulivoimalamelun on havaittu häiritsevän enemmän kuin tasaisten äänien. Moduloinnin aiheuttama häiritsevyyden lisäys voidaan huomioida lisäämällä mitattuun keskiäänitasoon sanktio. Tässä väitöskirjassa tutkittiin, tarvitaanko sanktiota jaksollisesti vaihtelevalle laajakaistaiselle melulle, jonka äänitaso on matala. Tätä tutkittiin toteuttamalla psykoakustinen kuuntelukoe, johon osallistui 40 koehenkilöä. Tulokset osoittivat, että sanktio voi olla tarpeen tietyllä modulaatiotaajuuden ja modulaatiosyvyyden arvoalueella. Sanktion suuruus kasvoi modulaatiotaajuuden ja modulaatiosyvyyden kasvaessa, mikä ei tue vakiosanktion käyttöä. Tämän väitöskirjan tuloksia voidaan hyyödyntää tieteellisessä tutkimuksessa sekä akustisten standardien ja rakennusmääräysten kehittämisessä.